Eculizumab Treatment for Postpartum HELLP Syndrome and aHUS—Case Report - Lokki, A. Inkeri; Haapio, Mikko; Heikkinen-Eloranta, Jenni (Frontiers in Immunology, 2020)
Preeclampsia is a pregnancy-specific disorder affecting ca 3% of all pregnant women. Preeclampsia is the source of severe pregnancy complications. Later life consequences for mother and infant include increased risk of cardiovascular disease. Preeclampsia is caused by the dysfunction of the endothelium with subsequent activation of complement and coagulation systems. HELLP syndrome is considered to be an extreme complication of preeclampsia but it can also present independently. Diagnostic symptoms in HELLP syndrome are Hemolysis, Elevated Liver enzymes and Low Platelets. Similar symptoms are present in thrombotic microangiopathies (TMAs) and HELLP syndrome is considered part of the TMA spectrum. Here we present a case of severe preeclampsia and HELLP syndrome, which exacerbated rapidly and eventually lead to need of intensive care, plasma exchange and dialysis. The patient showed signs of hemolysis, disturbance in the coagulation and organ damage in liver and kidneys. After comprehensive laboratory testing and supportive care, the symptoms did not subside and treatment with complement C5 inhibitor eculizumab was started. Thereafter the patient started to recover. The patient had pregnancy -induced aHUS. Earlier initiation of eculizumab treatment may potentially shorten and mitigate the disease and hypothetically decreased the risks for the future health of preeclamptic women.